Pengaruh Pinjaman KUR, Gadai Emas Dan Gadai Kendaraan Terhadap Peningkatan Produktifitas Umkm Mitra Binaan PT Pegadaian Cabang Pringgan Kota Medan - Andre Irawan; Jessin Candra Lim; Delpy Swasti Lase; Ali Jamil; Desi Faizal Mirza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine and analyze the effect of mortgage loans, gold pawning, and vehicle pawning on the productivity of MSMEs fostered by PT Pegadaian Pringgan Branch, Medan City. Improved business conditions are a consideration for PT Pegadaian in providing KUR loans, gold mortgages, and vehicle mortgages to increase MSME productivity, which can help businesses progress in the future. KUR loans are provided by the Indonesian government to support MSMEs in increasing their access to finance. The KUR loan is intended to finance working capital, investment, and the purchase of production goods for MSMEs. In the Gold pawn service, MSMEs pawn their gold to PT Pegadaian and will receive a loan according to the value of the gold. Vehicle Pawn allows MSMEs to borrow money by providing a vehicle, such as a car or motorcycle, as collateral. PT Pegadaian will evaluate the value of the vehicle and provide loans according to the collateral value. This study uses quantitative research, with a sample size of 71 respondents. Methods of data analysis using multiple linear regression Simple random sampling was used as the sampling method. The conclusion of this study is that credit loans partially have a positive and significant effect on the productivity of fostered partner SMEs of PT Pegadaian Pringgan Branch, Medan City; gold pawning partially has a positive and significant effect on the productivity of fostered partner SMEs of PT Pegadaian Pringgan Branch, Medan City; and pawning vehicles partially has a positive and significant effect on the productivity of umkm fostered partners of PT Pegadaian Pringgan Branch, Medan City. Simultaneously, credit loans, gold pawns, and vehicle mortgages have a positive and significant effect on the productivity of MSMEs fostered by the partners of PT Pegadaian Pringgan Branch, Medan City. Keywords: kur loans, gold pawn, vehicle pawn, msme productivity